How Far Has Our MSMEs Credit Underwriting Assessment in Indonesian Commercial Banks Progressed? - Stanislaus Arya Luhur Pambudi (Profesional Muda Cendekia Publishing, 2022)
The literature on credit underwriting assessment is huge, but many are designed for consumer banking. Given that most banks in Indonesia got their revenue from commercial banking activities, it is critical to recall the main characteristics of current practice as recorded in published papers with cases in Indonesia's MSMEs credit underwriting risk assessment. This study discusses the industry standard of loan origination framework and the emerging trend of statistical and advanced analytic methods with their challenges, focusing on papers on credit underwriting risk assessment with MSMEs datasets leaning on Indonesian data whenever available and opening research questions in this topic. Examples given in this paper may indicate the methods used by Indonesian banks to assess the creditworthiness of MSMEs, although there is no clue if either the mentioned studies are implemented in the respective banks or just for academic purposes.